Rice Farming for Food Security and Ecological Sustainability: A an Analysis of farmer’s Awareness in Kerala - K, Rejula.; Singh, Rashmi; Nain, M.S. (Indian Journal of Extension Education, 2017)
Rice is the staple food for more than 60 per cent of people in the world and also it is the choice crop for millions of poor and small farmers for income and household food security. Surprisingly, in India while rice production has increased (CAGR=3.32), area under paddy cultivation has not increased since 2002-03 to 2013-14. Among Indian states, Kerala has witnessed vast changes in cropping pattern and land use pattern recently. The share of agricultural land devoted to food crops, including rice was 37.5 per cent in 1981 which fell down to 12.5 per cent in the year 2006. Thus, there has been a major change in use of land for cultivating food crops and non-food crops in Kerala. The situation warranted State Government to formulate a special legislation to stop filling up of paddy fields for other cash crops cultivation or nonfarm uses. In this scenario, an analysis of farmer’s awareness regarding importance of paddy cultivation is very important. Present study was conducted in the state of Kerala among paddy farmers. Structured interview schedule was used for primary data collection. An ex-post facto research design was used for the study. Awareness of farmers regarding the importance of paddy lands in maintaining food security and ecological sustainability was measured using a test developed for the purpose. Secondary sources of information and expert opinion were used for developing items in the test. The test consisted of nine components and each component consisted of four sub questions. Reliability of test was calculated using Cronbach alpha test (Alpha=0 .765). Majority (54.58%) of the respondents had medium level of awareness (awareness index between 0.94 & 0.33) which signified that majority of respondents had acquired medium level of awareness about the ecosystem services of wetlands. 25.41 per cent of respondents had low awareness (awareness index between 0.33 & 0.02) about importance of paddy lands in maintaining food security and ecological sustainability. There was no respondent with very low level of awareness.Only 56.25 per cent of respondents had awareness about the actual scenario of food deficit in Kerala. Sediment and nutrient retention function and water purification function of rain fed paddy lands were known to comparatively less number of respondents. The minimum awareness was observed in the component true value of wetland resources. Only 43 per cent respondents knew the “true value of wetland resources”. Similarly water purification function is also unknown to majority of the respondents. Therefore, awareness generation should be given specifically concentrating this area, so that people start thinking rejuvenating the existing paddy fields.
Keywords: Paddy Land; Food Security; Ecology; Kerala; Awareness